Impact of PEWS on Perceived Quality of Care During Deterioration in Children With Cancer Hospitalized in Different Resource-Settings - Garza, Marcela; Graetz, Dylan E.; Kaye, Erica C.; Ferrara, Gia; Rodriguez, Mario; Soberanis Vásquez, Dora Judith; Méndez Aceituno, Alejandra; Antillon-Klussmann, Federico; Gattuso, Jami S.; Mandrell, Belinda N.; Baker, Justin N.; Rodriguez-Galindo, Carlos; et al. (Frontiers in Oncology, 2021)
BACKGROUND: Children with cancer are at high risk for clinical deterioration and subsequent mortality. Pediatric Early Warning Systems (PEWS) have proven to reduce the frequency of clinical deterioration in hospitalized patients. This qualitative study evaluates provider perspectives on the impact of PEWS on quality of care during deterioration events in a high-resource and resource-limited setting. METHODS: We conducted semi-structured interviews with 83 healthcare staff (nurses, pediatricians, oncology fellows and intensivists) involved in recent deterioration events at two pediatric oncology hospitals of different resource levels: St. Jude Children’s Research Hospital (SJCRH; n=42) and Unidad Nacional de Oncología Pediátrica (UNOP; n=41). Interviews were conducted in the participant’s native language (English or Spanish), translated into English, and transcribed. Transcripts were coded and analyzed inductively. RESULTS: Providers discussed both positive and negative perspectives of clinical deterioration events. Content analysis revealed “teamwork,” “experience with deterioration,” “early awareness,” and “effective communication” as themes associated with positive perception of events, which contributed to patient safety. Negative themes included “lack of communication,” “inexperience with deterioration,” “challenges with technology”, “limited material resources,” “false positive score,” and “objective tool”. Participants representing all disciplines across both institutions shared similar positive opinions. Negative opinions, however, differed between the two institutions, with providers at UNOP highlighting limited resources while those at SJCRH expressing concerns about technology misuse. CONCLUSION: Providers that care for children with cancer find PEWS valuable to improve the quality of hospital care, regardless of hospital resource-level. Identified challenges, including inadequate critical care resources and challenges with technology, differ by hospital resource-level. These findings build on growing data demonstrating the positive impact of PEWS on quality of care and encourage wide dissemination of PEWS in clinical practice.